Tailored polyelectrolyte thin film multilayers to modulate cell adhesion - Muzzio, Nicolás Eduardo (2017)
The layer-by-layer assembly of polyelectrolyte multilayers (PEMs) from natural or synthetic polyelectrolytes constitutes a very versatile and simple strategy to modify surfaces and modulate cell behavior. PEMs assembled from natural polyelectrolytes are very appealing for biological and medical applications due to their high biocompatibility. However, PEMs from natural polyelectrolytes display poor cell adhesion as they are soft materials with an elasticity modulus of a few kilopascal. In this report, the authors present results on the modulation of cell adhesion of different immortalized cell lines by PEMs. Two strategies are employed to vary cell adhesion: (1) a heterogeneous polyelectrolyte multilayer is assembled employing a rigid bottom block including a synthetic polyelectrolyte with a soft upper block of natural polyelectrolytes and (2) polyelectrolyte multilayers from natural polyelectrolytes are thermally annealed after assembly. The physicochemical characteristics of the PEMs change upon thermal treatment. Depending on the composition of the polyelectrolyte multilayer, cell adhesion may be enhanced or reduced. Based on the impact on PEM properties and cell adhesion caused by thermal annealing, a temperature gradient is applied to a PEM of poly-L-lysine/alginate to induce a spatial variation of PEM properties, resulting in a gradient in cell adhesion. The strategies shown here can be employed as simple alternatives to tailor PEM properties by means of fully biocompatible procedures.